The repellent effect of plants and their active substances against the beetle storage pests. (December 2017) - Kłyś, Małgorzata; Malejky, Natalia; Nowak-Chmura, Magdalena
Abstract: This review compares research techniques, plant species and forms of their application in worldwide studies on the repellent activity of plant material against storage pests, such as Sitophilus oryzae, Sitophilus granarius, Tribolium castaneum, Rhyzopertha dominica and Oryzaephilus surinamensis . Over 300 plant extracts, essential oils and powders were tested against these five insect species with various methods. The intensity of repellency of the examined plant products against each considered pest species was presented. Evaluation of the repellency potential of particular plant extracts, oils and powders showed that insect repulsion increased with their concentration. Duration of exposure was also an important factor affecting repellent activity. Highlights: Repellency increased with increasing dose of the plant materials for stored-grain pests. The exposure period the most important factor influencing the repellent effect. In studies of the repellent action of the plants using different of the test methods.